Eksistensi Penyuluh Bahasa Bali pada Masa Pandemi Covid-19 di Kecamatan Blahbatuh, Kabupaten Gianyar - Ni Nyoman Nur Aditya Maha Yogi; Relin D. E.; Made Iwan Indrawan Jendra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Penyuluh bahasa Bali are people having roles, duties, professions to provide education, guidance, and information to the community to overcome various problems related to the Balinese language. Blahbatuh District is one of the sub-districts in the Gianyar Regency region having a lot of history, is thick with traditions, arts and culture. Balinese language is one of the ancestral heritage that should be preserved. However, nowadays, along with the times, the Balinese language is considered difficult by most of the younger generation as stated by penyuluh bahasa Bali and the local community in Blahbatuh District. So that the presence of penyuluh bahasa Bali is very welcomed by the people of Blahbatuh District to be able to present programs that awaken and foster people's love for Balinese language, script and literature. The COVID-19 pandemic has hampered all sectors of life, including the preservation of Balinese language, script and literature. Penyuluh bahasa Bali during the COVID-19 pandemic faced several obstacles in carrying out their duties which could affect their existence, so that the existence of Balinese language, script and literature was also influenced by the existence of Penyuluh bahasa Bali.